Levelling playing field: synchronization and rapid facial mimicry in dog-horse play - Veronica Maglieri; Filippo Bigozzi; Marco Germain Riccobono; Elisabetta Palagi (Behavioural Processes, 2020)
Social play is a window on cognitive and communicative abilities of species. Inter-specific play, in particular, is a fertile venue to explore the capacity to correctly perceive and interpret signals emitted by partners. Up to now, most studies have focussed on dog-human play due to the important implications such studies have in understanding the peculiar relationship we establish with our pets. Here, we focussed on social play between dogs and horses. By using a set of specific keywords (dog, horse, play, friend) we selected 20 videos of dog-horse social play (with each session lasting>30 s) from the open video-sharing website YouTube. We described the behavioural patterns composing each session by defining analogous and species-specific patterns shown by dogs and horses. The rates of self-handicapping and variability in playful actions did not differ between the two interacting subjects thus suggesting well-balanced playful tactics. The Relaxed Open Mouth (ROM, a widespread playful facial expression in mammals) was also similarly performed by dogs and horses. The Rapid Facial Mimicry (RFM) is an automatic, fast response in which individuals mimic others’ expressions (less than 1 s) that seems to have a role in mood sharing during social interactions. The dogs and horses under study showed a stronger and rapid mimicry response (less than 1 s) after perceiving ROM than after perceiving an attempt to bite (a play pattern resembling ROM in its motor performance). Taken together, our results suggest that, despite the difference in size, the phylogenetic distance, and differences in the behavioural repertoire, dogs and horses are able to fine-tune their actions thus reducing the probability of misunderstanding and escalating into aggression. One of the future challenges is to explore the role of ontogenetic pathways and familiarity in shaping inter-specific communicative ability of animals that can be at the basis of a universal language of play